Measures of Health Provide Insights Into the Coping Strategies of Urban Lizards - Amdekar, Madhura S.; Kakkar, Aishwaarya; Thaker, Maria (Frontiers in Ecology and Evolution, 2018)
Abstract The rapid rate of urbanization worldwide and its consequences for affected species and ecosystems urgently warrants research and action. Whether animals are effectively coping from urbanization is hotly debated, especially since interpretations are based on different measures of animal responses. Here, we take a physiology-centric view of animal coping strategies, and set up predictions for distinguishing urban adaptors and exploiters using multiple markers of health. Our study compares rural and urban populations of a tropical lizard species, the Indian rock agama (Psammophilus dorsalis), that lives in a rapidly changing and highly threatened semi-arid ecosystem in Southern India. Contrary to expectations, we did not find any significant differences in body condition, number of ectoparasites, and degree of cell-mediated immune response between lizards from urban and rural areas, despite previously documented differences in aspects of their behaviour. However, urban lizards had lower heterophil to lymphocyte ratios, as well as lower testosterone levels compared to rural lizards, which suggest active physiological coping responses. Notably, we find no correlation between the different physiological measures within individuals; strongly reflecting the flexible and independent axes of health responsiveness. Overall, the considerable overlap in responses by urban and rural lizards highlights the importance of using multiple measures of immunity to evaluate health status. These data collectively indicate that P. dorsalis is an urban adaptor, and that the tropical urban environment is not associated with harmful consequences for their health.